Transarterial Chemoembolization Combined With Immune Checkpoint Inhibitors and Tyrosine Kinase Inhibitors for Unresectable Hepatocellular Carcinoma: Efficacy and Systemic Immune Response - Yang, Fei; Xu, Gui-Li; Huang, Jin-Tao; Yin, Yu; Xiang, Wei; Zhong, Bin-Yan; Li, Wan-Ci; Shen, Jian; Zhang, Shuai; Yang, Jun; Sun, Hong Peng; Wang, Wan-Sheng; et al. (Frontiers in Immunology, 2022)
Background: Locoregional therapy combined with systemic therapy can further improve the prognoses for HCC. However, it is still unknown the efficacy of TACE combined with ICIs and TKIs for HCC, and weather this triple therapy can activate systemic immune response. Purpose: To identify the efficacy of TACE+ICIs+TKIs for unresectable hepatocellular carcinoma (uHCC), and its effect on systemic immunity. Materials and Methods: This single center retrospective study was approved by the Institutional Review Board. From August 1, 2019, to March 30, 2021, patients with uHCC who received the combination therapy of TACE+ICIs+TKIs were included. Peripheral blood samples were collected at baseline and once a month for four months after treatment. Lymphocyte subsets were measured by flow cytometry; Immunoglobulins were measured using the immune turbidimetric method. The dynamic change trend of circulating parameters were tested using simple linear regression. Results: 53 patients with mean age of 59±10.6 years were included. TTP was 8.0 months (95%CI, 5.5～10.5) and PFS was 8.5 months (95%CI, 5.4～11.5). ORR was 52.8% and DCR was 81.1%. 20 patients had completed analysis of biomarkers in peripheral blood. For cellular immune response，the level of circulating CD8+, CD3+ T cells and NK cells increased, the frequency of CD4+T cells and the ratio of CD4+/ CD8+ decreased, among them, CD8+ T cells increased significantly. For humoral immune response, there was a significant decrease of B cells and significant increases of Ig G、Ig κ and Ig λ. Moreover, Ig G, Ig κ and Ig λ were related to tumor response. Conclusion: TACE + ICIs +TKIs showed considerable efficacy in patients with uHCC. This triple therapy activated not only cell immune but also humoral immune activation. Circulating Ig G，Ig λ and Ig κ can be served as potential biomarkers.